Minimum wage policy in Great Britain and the United States - Waltman, Jerold L., 1945- (Algora Pub., 2008)
Analyzing wage policies and the political ideas that underlie them, including the irony of an Iraq funding bill leading to a minimum wage increase, this book compares not only Federal but State minimum wage policies and those of Britain as well. Going beyond the debate on public expenditure programs, the author examines the future of the "welfare state"? not from a perspective of entitlement but of citizenship in a public polity.